Bisexual Identity in a Religious Environment in Christina Lauren’s Autoboyography - A. Sasli, Siti Atiqahgania; Setiawan, Ikwan; Salikin, Hairus (Universitas Airlangga, 2024)
This study focuses on analyzing the representation of bisexual identity in Christina Lauren’s novel